Responses of Phalaris canariensis L. exposed to commercial fuels during growth - Patat, María Laura (2014)
The growth behavior of canary grass (Phalaris canariensis L) when cultivated in presence of farming fuels is reported in this work. P. canariensis L. is relevant in several countries. It is an emergent plant for phytoremediation and biofuel activities. The following variables: root length, stem length, total plant weight, green tissue weight (tiller, leaf), and total chlorophyll and chlorophyll a/b ratio, were monitored during the growth in presence of commercial fuels (premium grade, regular grade, diesel, and kerosene) at different concentrations. We applied a comprehensive statistical analysis to understand the results: Univariate analysis, factorial analysis of variance, and subsequent Tukey test were applied to the variables to assess the significance of the differences found. The normality of these variables was analyzed with the Shapiro Wilk test. All parameters were affected by all type and concentrations of fuels and its interaction. This is one of the first reported cases which describe the growth parameters responses fromcanary grass when cultivated in presence of an essentially constant concentration of farming fuels.